(untitled) (Research, Society and Development, 2022)
Objective: to identify the main changes in skin integrity in the face of the use of personal protective equipment (PPE)/paramentation and to determine the incidence rate of these changes. Methodology: descriptive exploratory research with quantitative approach. Data collection occurred in January 2022, through a data collection form with open and closed questions. The sample was composed of professionals whose inclusion criterion was the use of PPE/paramentation against the COVID-19 pandemic. The research site was a university hospital in Rio de Janeiro. Results: 84 professionals answered the data collection form, 66.7% female and 33.3% male. The main changes in skin integrity were: 84% of the participating health professionals reported hyperemia (redness), 85% marks on the skin by pressure, 36% lesions, 57% increased moisture in the skin and 23% stated that they had some unspecified dermatological alteration. The PFF2 mask of type N95 was the EPI most cited as causing dermatological alterations. Conclusion: The need for continuous use of PPE/paramentation, for long periods and sometimes without respecting prevention measures, determined the emergence of dermatological changes due to external risk factors such as pressure, friction and alteration of the skin microclimate, as intervening variables of skin integrity breakdown. Therefore, actions of occupational health education are recommended so that all professionals, in order to recognize risks, identify injuries resulting from the use of PPE/paramentation and thus avoid them during their work activities.